The Relationship Between Quality of Sleep in Pregnant Women With the Incidence of Preeclampsia - Muliatul Jannah; Rr. Catur Leny; Qonita Irawan Qonita (Jurma : Jurnal Program Mahasiswa Kreatif, 2023)
during pregnancy, pregnant women often have difficulty sleeping due to physical changes and stress control, and even experienced depression. The older the pregnancy, the higher the risk of sleep disorders. Several factors can cause blood pressure to be high during pregnancy, including quality sleep. Pregnancy hypertension is experienced by 8% of pregnant women which is the cause of death of mothers and neonates at risk of eclampsia and pre-eclampsia. High blood pressure during pregnancy can affect the quality of sleep. Insomnia is experienced by 12% of pregnant women in the first trimester and as many as 75% at the end of pregnancy. Objective: This Literature review aims to determine the relationship of sleep quality to changes in blood pressure of pregnant women resulting in the incidence of preeclampsia. Method:Flowchart database search from Google Scholar, Pubmed, and Science Direct was conducted in 2018-2023, and can be accessed for free, with the search word (((((Quality Sleep) OR (pregnant women)) AND (preeclampsia*)) OR (maternity mothers*)) AND (blood pressure) then the selected article after the selection results are 6 articles. Result: pregnant women have poor sleep quality, especially because it also affects changes in blood pressure that tends to increase in pregnant women who have poor sleep quality, factors that affect sleep quality include stress, environment, race, age, and medical history. Conclusion: there is a relationship between the quality of sleep with changes in blood pressure in pregnant women as evidenced in pregnant women who have poor sleep quality getting the results of a systolic and diastolic increase in blood pressure, this can increase the risk of preeclampsia if not treated immediately.